Trend of Tuberculosis Cases under DOTS Strategy in Dakshina Kannada District Of Karnataka, India: Issues and Challenges - S Ganesh Kumar; HN Harsha Kumar; Rao Ramakrishna; S Jayarama; MS Kotian (Tehran University of Medical Sciences, 2009)
Background: Tuberculosis remains a worldwide public health problem and India accounts for highest TB burden in the world. The aim of the study was to evaluate the trend and treatment outcome of tuberculosis (TB) cases treated under DOTS strategy at a district level in Karnataka, India. Methods: This was a Retrospective record based study conducted in Dakshina Kannada district of Karnataka, during January 2007 to April 2007. Patients registered for treatment in the entire district since its inception in 2003 to 2006 were considered for analysis. Results: Totally, 7620 patients were treated under DOTS strategy. Of these, 3308 cases (43%) were found to be new sputum smear positive for acid-fast bacilli (AFB). The case notification rate has increased from 55% in 2003 to 85% in 2005.  The incidence of new sputum positive TB cases were maximum among productive age group (15-44 years) and was significant (χ2= 150.08, P=< 0.001). Males constituted 70% of the total new sputum positive TB cases and the difference seen in males and females was also statistically significant (χ2= 551.254, P< 0.001). Defaulter cases have been increasing among new smear positive cases and this was statistically significant (χ2=4.9, P= 0.03). Conclusion: The cure rate is declining along with the increasing default rate among new smear positive cases over a period.